2007
DOI: 10.1007/s10290-007-0111-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Current Account Imbalances in 16 OECD Countries: An Out-Of-Sample Perspective

Abstract: Current account dynamics, panel data models, heterogeneity, prediction,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, Calderon, Chong, and Loayza 4 See Brook et al 2004;Barnett and Straub 2008;Liang 2012;Kandil and Greene 2002;Edwards 2005;Bems, Dedola, and Smets 2007;Fratzscher, Juvenal, and Sarno 2007. 5 See Khan and Knight 1983;Debelle and Faruqee 1996;Elliot and Fatas 1996;Milesi-Ferretti and Razin 1998;Calderon et al 2002;Giuliodori 2004;Chinn and Prasad 2003;Herwartz and Siedenburg 2007;Ang and Sek 2011. Downloaded by [University of Otago] at 22:32 15 March 2015 investigated the link between a broad set of economic variables and current account deficits in forty-four developing countries for the period of 1966-94 by using panel data analysis. The results point out that increases in domestic output growth, movements in the terms of trade, and rising real exchange rates will lead to higher current account deficits.…”
Section: Literature Surveymentioning
confidence: 98%
“…On the other hand, Calderon, Chong, and Loayza 4 See Brook et al 2004;Barnett and Straub 2008;Liang 2012;Kandil and Greene 2002;Edwards 2005;Bems, Dedola, and Smets 2007;Fratzscher, Juvenal, and Sarno 2007. 5 See Khan and Knight 1983;Debelle and Faruqee 1996;Elliot and Fatas 1996;Milesi-Ferretti and Razin 1998;Calderon et al 2002;Giuliodori 2004;Chinn and Prasad 2003;Herwartz and Siedenburg 2007;Ang and Sek 2011. Downloaded by [University of Otago] at 22:32 15 March 2015 investigated the link between a broad set of economic variables and current account deficits in forty-four developing countries for the period of 1966-94 by using panel data analysis. The results point out that increases in domestic output growth, movements in the terms of trade, and rising real exchange rates will lead to higher current account deficits.…”
Section: Literature Surveymentioning
confidence: 98%
“…In addition, some critical test results were found by the authors, indicating that none of these two theories were valid. Herwartz & Siedenburg (2007) tested the data of 16 OECD countries in the period 1980-2004 with panel regression and dynamic panel method. According to the findings, the effects of the variables of public sector budget balance, national output deficit and terms of trade on the current account balance are essential.…”
Section: (X − M) = (Y − C − T) + (T − G) − I = Sp + Sg -Imentioning
confidence: 99%
“…Their empirical findings revealed that a negative relationship exists between the movements of the real effective exchange rate and current account in majority of EMU countries after accounting for the role of the income growth. Herwartz and Siedenburg (2007), on the other hand, based their study on Debelle and Faruqee (1996) to uncover the determinants of current account imbalances. Since fixed effect evaluation of current account determinants may suffer from slope heterogeneity, they employed mean group estimation for a panel of 16 OECD countries covering the period 1980–2004.…”
Section: Literature Reviewmentioning
confidence: 99%